Volcanism of the Late Silurian Eastport Formation of the Coastal Volcanic Belt, Passamaquoddy Bay, New Brunswick: GAC–MAC Halifax 2022 Pre-Meeting Field Trip - Van Wagoner, Nancy; Fyffe, Les; Lentz, David; Dadd, Kelsie; McNeil, Wayne; Baldwin, Diane (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2022)
This field trip is an excursion through the exquisite, nearly pristine exposures of a Silurian, felsic-dominated bimodal volcanic and sedimentary sequence exposed in the Passamaquoddy Bay area of southwestern, New Brunswick (Eastport Formation). These rocks form the northwest extension of the Coastal Volcanic Belt that extends from southwestern New Brunswick to the southern coast of Maine. The sequence is significant because it is part of a large bimodal igneous province with evidence for supervolcano-scale eruptions that began to form during the close of the Salinic Orogeny (about 424 Ma), and continued into the Acadian Orogeny (421–400 Ma). The geochemical characteristic of the rocks can be explained by extension related volcanism but the specific drivers of the extension are uncertain. The Passamaquoddy Bay sequence is 4 km thick and comprises four cycles of basaltic-rhyolitic volcanism. Basaltic volcanism typically precedes rhyolitic volcanism in Cycles 1–3. Cycle 4 represents the waning stages of volcanism and is dominated by peritidal sediments and basaltic volcanics. A spectrum of eruptive and emplacement mechanisms is represented ranging from the Hawaiian and Strombolian-type volcanism of the basaltic flows and pyroclastic scoria deposits, to highly explosive sub-Plinian to Plinian rhyolitic pyroclastic eruptions forming pyroclastic density currents (PDC) and high grade rheomorphic ignimbrites. During this field trip we will examine key exposures illustrating this spectrum of eruptive and emplacement processes, and their diagnostic characteristics, along with evidence for the interaction between mafic and felsic magmas and a variety of peperitic breccias formed as a result of emplacement of flows on wet peritidal sediments. The constraints the depositional setting and voluminous bimodal volcanism places on tectonic models will also be considered.